Study of Suspension Concentration Effect to The Electrical Resistance of Zinc Sulphophthalocyanine (ZnPcSn) Thin Film as Prototype of Ozone Detector - Ratnawati, Dhesy Galuh; MASRUROH, Masruroh; Tjahjanto, Rachmat Triandi (Chemistry Department, The University of Brawijaya, 2014)
We have studied the fabrication of zinc sulphophthalocyanine (ZnPcSn) thin film as prototype of ozone detector. The aim of this research is to find the relation between the electrical resistance of ZnPcSn thin film and the ZnPcSn suspension concentration. The thin film of ZnPcSn was deposited on Printed Circuit Board (PCB) substrate by using spin coating method, then, annealed at temperature of 100 oC. The resistance of ZnPcSn thin film was measured as it was exposed with ozone, synthesized from fresh air, for 60 min continuously. The electrical measurement was conducted twice for each point of data. The result of this research shows that the electrical resistance of ZnPcSn thin film decreases during the ozone exposure, and, it can be concluded that as the concentration of ZnPcSn suspension concentration increase, more amount of ozone can be adsorbed by thin film.